Drama as a means of facilitating adult learning in rural areas: South Africa case studies at Akanani - Blues, Tracy (My University, 2016)
This research report examines the nature of drama as a means of facilitating adult learning, especially in the South African rural context, by conducting a literature review and by compiling case studies of the use of drama at Akanani, an association. of rural development projects in South Africa where theatre-for-development is the principal methodology employed. The literature review explores the use of drama as a methodology in education and then focuses on how and why theatre-for-development has been used in Africa for community development and empowerment. The international developments in popular theatre are also considered so that as much information as possible can feed into the guidelines which are this report's conclusions. This chapter concludes with a consideration of how drama can be used for adult learning in South Africa. This research was conducted primarily by compiling a number of case studies of the use of drama at Akanani in the far northern Transvaal. Participant observation, illuminative evaluation and semi-structured interviews were used within a Participatory Research apprgach to gather information about Akanani. The researcher spent two periods of time at Akanani conducting the interviews and observing the daily operations as well as the use of drama in various contexts at Akanani. The cases studies were compiled to discover whether drama, as it is used at Akanani, is a successful and appropriate methodology for adult education in the rural areas of South Africa. This research finds drama to be a a very effective means of facilitating learning amongst adults in rural areas and concludes by offering guidelines for the use of drama as a methodology in adult education in South Africa, especially in the rural areas.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Education (Coursework and Research Report), University of the Witwatersrand.
Keywords: Adult learning -- South Africa.; Drama in education -- South Africa.; Education, Rural -- South Africa.; Blacks -- Education -- South Africa.